The aesthetics of textual bonding in the poetry of Ibrahim Zeid Al-Kilani study in the diwan "Wamadat" - kerbaa, hocine; sadia, naima (El Omda in Linguistics and Discourse Analysis, 2025)
that contribute to textual connectivity, so we will study the most prominent of them through the poems of the Diwan "wamadat" by Ibrahim Zaid Al-Kilani by description and analysis. In this context, the article went towards the discourse/poetic text, as an artistic practice that shows a poetic experience, carrying sensory and moral issues, penetrating within it to study its interdependence, and we wanted to devote the study to the impact of interdependence in the cohesion of the Arabic poetic text through the chosen model, how it was done in achieving the poet's goals, strengthening the bonds of his poems, and combining their joints